Violencia conyugal en parejas con convivencia monogámica. - Funes Alvarado, Carmen Marchelly
ABSTRACT: This thesis is an analysis of the dynamics of violence and generating control processes within married life, by exploring the experience of five couples in conflict. The main findings are categorizing these situations of co-existence, which was built based on counseling theories, interviews with psychologists and specialists. The main categories are: gender, power, violence, religion, communication, psychology, therapy and socio-culture, three of which contain the dynamic violence generation and control processes: power, violence and religion. The themes that emerged from the research findings are: the household economy as a trigger of crisis, socio-cultural heritage on the distribution of activities in the house, sexuality when only satisfies one of the partners and religion as driver crisis. Keywords: Process control, dynamic generation of violence, domestic violence. RESUMEN: La presente tesis es un análisis de las dinámicas generadoras de violencia y de los procesos de control dentro de la convivencia conyugal, mediante la exploración de la experiencia de cinco parejas en conflicto. Los hallazgos principales son la categorización de estas situaciones de convivencia, la que fue construida con base a teorías orientadoras, entrevistas con las parejas y con sicólogos especialistas. Las categorías principales son: género, poder, violencia, religión, comunicación, psicología, terapia y sociocultura, de las cuales tres encierran las dinámicas generadoras de violencia y los procesos de control: el poder, la violencia y religión. Las temáticas surgidas de los hallazgos de la investigación son: la economía del hogar como detonante de crisis, herencia sociocultural sobre la distribución de las actividades en el hogar, la sexualidad cuando solo satisface a uno de los miembros de la pareja y la religión como controlador de crisis. Palabras claves: Procesos de control, dinámicas generadoras de violencia, violencia conyugal.